THU0636 HIGHER SOCIAL MEDIA USER STICKINESS ON SELF-MANAGEMENT SYSTEM MAY IMPROVE THE REMISSION RATE OF PATIENTS WITH ANKYLOSING SPONDYLITIS. (June 2019) - Ji, Xiaojian; Zhu, Jian; Zhang, Jianglin; Huang, Feng; ,
Abstract : Background: With the advence of mobile health technologies, it is possible to set up economic management systems to improve health care. By using a Smart-phone Spondyloarthritis Management System (SpAMS), the Chinese Ankylosing Spondylitis (AS)/Spondyloarthritis Prospective Imaging Cohort (CASPIC) was launched. Objectives: To explore the improvement of disease management and cost effectiveness of SpAMS for Chinese patients with AS. Methods: Patients enrolled in the CASPIC cohort who fulfilled the 1984 modified New York criteria and with at least 2 evaluations of Ankylosing Spondylitis Disease Activity Score (ASDAS) were included in this analysis. All physician-reported assessments were collected at the Chinese People's Liberation Army General Hospital using SpAMS in Beijing. The disease activity states were defined according to ASDAS1, which separated inactive disease (ID) from low disease activity (LDA) by 1.3, LDA from high disease activity (HDA) by 2.1, and HDA from very high disease activity (VHDA) by 3.5. According to ASDAS at the baseline visits and final visits, patients were divided into four groups (Figure 1 ): maintainer of ID/LDA, patients with relapse, maintainer of active disease, and new achiever of ID/LDA. Results: From April 2016 to April 2018, 1201 patients with AS were enrolled in CASPIC. 4659 patient self-assessments were completed, including 3304 pre-visit assessments and 1355 assessments during the follow-up interval. After online consultation, 29.1% of clinic visits to a tertiary hospital were considered unnecessary and could be solved in the primary care hospital. The time and cost of each patient's journey to Beijing were calculated based on the location of each patient. For the 1037 (86.3%) patients who lived outside the vicinity of Beijing, at least an average of 5.3 hours and 327.4 RMB for each person (USD: RMB =1:6.418) for traffic time and expenses were saved, which equaled to 16% of the Chinese monthly disposable personal income (data in 2016). Of these patients enrolled in CASPIC, 777 patients had at least 2 evaluations of ASDAS. The rate of patients with ID/LDA was 57.2% at baseline and increased significantly to 79.2% with a mean (SD) follow-up of 13.3 (5.9) months (Table 1 ). Compared with patients who relapsed, those that maintained the ID/LDA had more patient assessments [5.0 (2.7) vs 3.3 (1.8), P < 0.001]. The new achievers of ID/LDA also completed online patient assessments more frequent [5.6 (3.1) vs 4.5 (2.5), P < 0.001] compared to patients who maintained active disease. Conclusion: Higher social media user stickiness on self-management system may improve the remission rate of AS patients. SpAMS could serve as a cost- and time-saving specialty care online platform for patients with AS. References: [1] Machado PM, Landewé R, Heijde Dvd. Ankylosing Spondylitis Disease Activity Score (ASDAS): 2018 update of the nomenclature for disease activity states. Ann Rheum Dis 2018:annrheumdis-2018-213184 Disclosure of Interests: None declared